(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
Polycrystalline NiFe2O4 samples were prepared from analytical grade powder of NiO and Fe2O3 by conventional double sintering technique. The samples were sintered at 1000 - 1400°C. The scanning electron micrographs (magnification ´ 10000) of the samples revealed that the grain size increases and the porosity decreases with the increase in sintering temperature. These changes in microstructure, grain size and porosity with sintering temperature have great influence on the magnetic properties of NiFe2O4. Complex permeability (u) over the frequency range from 1 kHz to 13 MHz for the samples at different sintering temperatures (1000-1400°C) has been observed. Variation of permeability with the applied temperature has been observed at various sintering temperature from which Curie temperature have been calculated. Decreased value of Curie temperature (Tc) has been found with the increase of sintering temperature. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 1, 59-64, 2015